Отверженная: [роман] / Пози Грэм-Эванс - Грэм-Эванс Пози (Мир книги, 2008)
Экземпляры: аб. Камская библиотека (20210317) / Инвентарный номер: 9485 / Цена: / Сис.шифр: 84(7Сое) / Авт.знак: Г 91 / ГРНТИ: 17.82.31 / ББК: 84(7Coe)